2020
DOI: 10.7717/peerj.9301
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prognostic risk factors for pancreatic cancer using bioinformatics analysis

Abstract: Background Pancreatic cancer is one of the most common malignant cancers worldwide. Currently, the pathogenesis of pancreatic cancer remains unclear; thus, it is necessary to explore its precise molecular mechanisms. Methods To identify candidate genes involved in the tumorigenesis and proliferation of pancreatic cancer, the microarray datasets GSE32676, GSE15471 and GSE71989 were downloaded from the Gene Expression Omnibus (GEO) database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…It is worth noting that DEGs in PDAC have already been demonstrated in several studies 6,7 . However, the results were not consistent, which could be due to the differences in the selection of datasets and statistical procedures.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…It is worth noting that DEGs in PDAC have already been demonstrated in several studies 6,7 . However, the results were not consistent, which could be due to the differences in the selection of datasets and statistical procedures.…”
Section: Discussionmentioning
confidence: 77%
“…The gene expression profiles from diverse microarray platforms are submitted to several public databases, including Gene Expression Omnibus (GEO: https://www.ncbi.nlm.nih.gov/gds/). Several previous studies used gene expression microarray technology to underpinning the DEGs of PDAC in recent years 6,7 . However, the results were inconsistent, and various aspects remain unclear due to sample heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, based on the analysis of the TCGA data, we identified RRM2 mRNA expression as an independent negative prognostic factor for OS in pancreatic adenocarcinoma patients. By in silico analysis of microarray-based gene expression data, Jin et al [ 32 ] have reported similar poor prognostic effect of RRM2 for PDAC, but with regard to disease-free survival (DFS; univariate Kaplan–Meier analysis). Correspondingly, in the cohort study by Itoi et al [ 28 ], high transcript expression of RRM2 in 31 fine-needle aspiration biopsy specimens of advanced stage pancreatic cancer significantly correlated with a poor patient survival and resistance to gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“…Besides a few rather small-scale experimental studies in various cancer types, e.g., breast ( 21 ), ovarian ( 22 , 40 ), cervical ( 41 ) and prostate ( 25 ) carcinomas, Big Data mining, from the Gene Expression Omnibus (GEO) or the Cancer Genome Atlas (TCGA) databases, using various in silico bioinformatics have demonstrated that some cytokinesis regulators may have prognostic value alone or as a part of a specific gene sets ( 50 52 ). For example, KIF14 is one of 10 genes whose low transcript expression in the GSE62452 microarray dataset, composed of 69 PDAC tumors predicted significantly poorer OS time of patients with PDAC and this was also observed in the TCGA RNASeq dataset ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, KIF14 was reported among 7 metastasis-related genes with prognostic potential based on OS time in PDAC based on 141 patients from the TCGA dataset validated with the GSE62452 dataset ( 51 ). Additionally, PRC1 is among 10 other genes whose signature predicts OS time and 12 genes predicting disease-free survival time of patients with PDAC based on in silico analysis of data of 77 patients with PDAC from 3 GEO datasets ( 52 ). High intra-tumoral CIT transcript level alone was recently identified as poor prognosis predictor (both OS and disease-free survival time) in PDAC through analysis of 178 patients from the TCGA dataset using the Gene Expression Profiling Interactive Analysis online tool ( 53 ).…”
Section: Discussionmentioning
confidence: 99%